Konsep al-Insān dalam Perspektif Hadis dan Implikasinya terhadap Pendidikan Islam - Azdillah, Muhammad Rizky; Dayusman, Edo Alvizar (Pascasarjana IAIN Lhokseumawe, 2025)
One of the key terms used in the Qur’an and Hadith to describe human beings is al-Insān, which reflects the spiritual, intellectual, and moral potential that can be developed through education. This study aims to explore in depth the meaning and characteristics of al-Insān as portrayed in the Hadith of Prophet Muhammad (peace be upon him), and to examine its implications for curriculum design and learning strategies in Islamic education. The research employs a qualitative approach using the library research method. Primary data were obtained from Hadiths relevant to the concept of humanity and education, while secondary data were drawn from scholarly literature discussing Islamic educational philosophy, prophetic values, and theories of human potential development. The analysis was conducted through descriptive, textual, and reflective approaches to interpret the meaning and educational relevance of al-Insān. The findings reveal that al-Insān in Hadith is depicted as a being endowed with intellect, soul, heart, and moral responsibility, functioning both as a servant of God and a steward on earth. Prophetic values such as honesty, commitment, and compassion form the core of character development in learners. The concept of al-Insān al-Kāmil—the perfected human—emerges as the ultimate goal of Islamic education, necessitating a value-based curriculum and balanced learning strategies that foster both spiritual and intellectual dimensions. Thus, the concept of al-Insān in the Hadith provides a strong conceptual foundation for Islamic education, aiming to cultivate individuals who are faithful, knowledgeable, and morally upright.